Augmented Reality sebagai Metafora Baru dalam Teknologi Interaksi Manusia dan Komputer - Teguh Martono, Kurniawan (JURNAL SISTEM KOMPUTER, 2011)
This paper contains about how the augmented reality technology used in new metaphors in computer interaction technology. Metaphor is one form of change. With changes in the field of interaction it will improve the user experience when operating the application. Augmented reality is the additional reality that is used to blend or combine objects in the virtual world with real-world environment. By using this technology are expected participation of users in interacting with existing applications, various fields such as military, health, education and other fields of applied science which has been implemented as part of augmented reality technology in its environment. Using augmented reality technology is expected to application users will feel the direct interaction process.KeywordsAugemented Reality; Interaction; Metafora